Pemanfaatan Buah Pepaya Menjadi Keripik Dan Digitalisasi Marketing Di Desa Lelede Kecamatan Kediri Kabupaten Lombok Barat NTB - Hj. Erviva Fariantin; Rusdi; Syaiful Amri; Indah Ariffianti; Elvina Setiawati; Sopian Saori; Dedy Febry Rachman (Valid Jurnal Pengabdian, 2024)
The aim of this service is to utilize papaya fruit to make papaya chips and digitize marketing in Lelede Village, Kediri District, West Lombok Regency, NTB. We know that papaya can not only be consumed directly but can also be processed into various foods, one of which is "Papaya Chips" or "Papaya Chips". The presence of papaya chips has become a food choice that can be consumed by all groups, from children, teenagers to adults. This papaya chips product or "Papaya Chip" is considered very appropriate to meet the need for healthy snacks, because consumers are now increasingly smart and aware of health, and are willing to spend time paying attention to types of natural products, so that business opportunities are expected. This can be utilized by people who already have a business or who are about to set up a business to increase income to survive which is increasingly difficult. The method of implementing this service is carried out in three stages, namely the planning stage, implementation stage and evaluation stage. The results of the service are the activity of making papaya chips which includes the acquisition of raw materials, goods in process and finished goods with simple quality control. The production process can also be carried out in everyday life because the ingredients are easy to obtain, by using papaya fruit that is around us we can produce papaya chips and these chips can be marketed so that they can help the family's economic income.